2005
DOI: 10.1021/np040237z
|View full text |Cite
|
Sign up to set email alerts
|

Merosesquiterpenes from Two Sponges of the Genus Dysidea

Abstract: The chemical study of two sponges of the genus Dysidea collected in the Gulf of California has led to the isolation of the new merosesquiterpenes 20-O-acetyl-21-hydroxy-ent-isozonarol (2), 20-O-acetylneoavarol (3), ent-yahazunol (4), and dysienone (5), together with the known compounds 1 and 6-9. The structures of the new metabolites have been established by spectroscopic techniques. The absolute configuration of compounds 5 and 6 has been investigated by application of a procedure developed by Riguera et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…Many of them have significant bioactivities, such as antibacterial, 9,[13][14][15] anti-inflammatory 16 and cytotoxic. 17,18 In our study of the bioactive compounds from marine sponges, two new (1, 2) and two known (3,4) alkaloids were isolated from the marine sponge Dysidea sp. The structures of two new metabolites were elucidated by interpretation of spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…Many of them have significant bioactivities, such as antibacterial, 9,[13][14][15] anti-inflammatory 16 and cytotoxic. 17,18 In our study of the bioactive compounds from marine sponges, two new (1, 2) and two known (3,4) alkaloids were isolated from the marine sponge Dysidea sp. The structures of two new metabolites were elucidated by interpretation of spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…3) These compounds have attracted much interest due to their structural diversity and varied biological activities, including anti-human immunodeficiency virus (HIV), 4) antibacterial, 5) antifungal, 6) antioxidative, 7) antitumor, 8) anti-inflammatory, 9) inhibition against protein tyrosine kinase (PTK) and protein tyrosine phosphatase 1B (PTP1B), 10,11) and activation of hypoxia-inducible factor-1 (HIF-1) activities. 12) During our search for bioactive metabolites from tropical sponges, we encountered a purple-colored encrusting Dysidea sp.…”
mentioning
confidence: 99%
“…Based on the cyclization between sesquiterpenoid and 3,5-dimethylorsellinic acid (DMOA) units, as well as the rearrangement of DMOA, the type of tetraketide-MSRDs can be further classified into five subgroups (SG I-V), namely citreohybridones , terretonins (148)(149)(150)(151)(152)(153)(154)(155)(156), andibenins (157)(158)(159)(160)(161)(162)(163), autins , and others (194)(195)(196)(197)(198)(199). Isotope labeling experiments revealed that they were all formed through the alkylation of DMOA by FPP as a key step [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102].…”
Section: Tetraketide-msrds Derived From 35-dimethylorsellinic Acidmentioning
confidence: 99%
“…15) refers to those in which the sesquiterpenoid and DMOA moieties are linked by only one C-C bond. Tropolactones A-D (196)(197)(198)(199) were isolated from the broth extract of a marine-derived fungus of Aspergillus genus. Novofumigatonin (195) was isolated from Aspergillus novofumigatus [143].…”
Section: Tetraketide-msrds Derived From 35-dimethylorsellinic Acidmentioning
confidence: 99%
See 1 more Smart Citation